Heterozygous Mutation in Adenosine Deaminase Gene in a Patient With Severe Lymphopenia Following Corticosteroid Treatment of Autoimmune Hemolytic Anemia - Tripodi, Serena I.; Corti, Paola; Giliani, Silvia; Lanfranchi, Arnalda; Biondi, Andrea; Badolato, Raffaele (Frontiers in Pediatrics, 2018)
We describe a previously healthy 14- year-old girl with acute onset autoimmune hemolytic anemia, associated with severe but transient lymphopenia during corticosteroid therapy, without infectious episodes during follow-up. After detailed investigations to rule out an underlying immunodeficiency, we detected a heterozygous ADA gene mutation. This was associated with slightly increased blood levels of adenosine and deoxyadenosine nucleotides and with reduced ADA activity in red blood cells, but within the normal range. This observation suggests that heterozygous ADA mutation might be a predisposing factor for lymphopenia in patients receiving corticosteroid therapy.